The Reception of the Novel La princesse de Clèves by Madame de La Fayette in the former Yugoslavia Area (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper analyzes the reception of Madam de Lafayette’s novel La Princesse de Clèves (1678) in the literary criticism of the former Yugoslavia The first part of the paper furnishes general information concerning life and work of the novelist, as well as the translations of her most important novel in Serbo-Croatian. The main part of the work examines in chronological order its critical reception in monographs, prefaces, reviews and scientific articles in literary periodicals since 1912. The results of the research show that the critical responses to the novel are satisfactory in volume and in quality and mainly correspond to the opinion of the French critics, besides the fact that there has been a larger period without critical writings (in the last three decades of the 20th century) and despite the lack of the analyses based on more contemporary critical theories (such as the perspectives of feminist and gynocritical theories, which have existed in foreign literary criticism since the last decade of the twentieth century).
Keywords: Madame de Lafayette; Princesse de Clèves; novel; critical reception; Serbo-Croatian literary criticism